PERBEDAAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF NHT DENGAN PEMBELAJARAN KONVENSIONAL (JURNAL ECONOMICA : Research of Economic And Economic Education, 2013)
This study aims to determine differences in student learning outcomes using cooperative learning model NHT with conventional learning in the high school class X Adabiah 2 Padang. The sampling technique is purposive sampling. The instrument used in this study is the achievement test. Form of test used is an objective form. The study finding there is difference between Economic Study Results Using Learning Model type Cooperatif Numbered Heads Together ( NHT ) with Conventional Learning High School Class X Adabiah 2 Padang